Impact of scabies on Indonesian public boarding school students’ quality of life: A mixed-method analysis - Menaldi, Sri Linuwih SW; Surya, Danny; The, Valensia Vivian; Marissa, Melani (UI Scholars Hub, 2021)
Background: Scabies is a neglected tropical disease in which people affected primarily presents with intense pruritus. The disease is often recurrent, especially in people living in close contacts, such as in a community; thus, it negatively impacts their quality of life (QoL).This study analyzes the impact of pruritus in scabies on the QoL of patients living in a public boarding school (PBS) in West Java, Indonesia. Methods: This study is a mixed-method study conducted on 39 subjects. TheQoL was examined using the Indonesian version of the dermatology life quality index (DLQI) questionnaire and in-depth interviews. Results: Most subjects were female, grade 9 students, had a duration of symptoms between six months to one year, had been infected more than twice, and with no family member affected by the same symptoms. We found that sex, duration of symptoms, disease frequency, and affected family members did not significantly affect subjects’ QoL. In-depth interviews revealed that pruritus affected social relationships, quality of learning, and sleeping. Conclusion: Holistic and comprehensive community management is needed to treat and prevent scabies transmission, as its symptoms negatively impact the QoL of students in PBS.